Annual Report of the Registrar 2004/2005 (2005)
Contents: --Definitions --Annual Report Data --Summary of Attendance --Attendance by Session --Full-time Equivalency Enrollment --Degrees Granted --Degree Summary --Program Certificates --Pupils in Price Laboratory School --Miscellaneous Enrollment Information --Degrees Granted by College, Degree Objective, and Racial/Ethnic Classificatio